What factors influence the decision of entrepreneurs in choosing a business incubator?. (2nd September 2020) - Carvalho, Luísa; Viana, Adriana Backx Noronha; Mine, Marcio
Often, start-ups reveal problems with asymmetric information that could be mitigated by a business incubator (BI). BIs can support new businesses, from creation through development and growth. This research aims to answer the follow research question: how is the decision-making of the incumbent firms influenced by the services and facilities offered by each BI? To achieve the objective of the research we used a sample of 39 start-ups incubated in Brazil and Portugal collected in Portugal (Lisbon) and Brazil (São Paulo). This study employs a survey to investigate how the decision of incubated start-ups for a BI were influenced by services and facilities available there. Descriptive statistics and correlation tests between the phases of the incubation process were applied. The results suggest the existence of a coherent relation between the incumbents' decisions on a BI and the services offered.